Effect of Facial Mask Treatment on Sutures Evaluated Through Single Photon Emission Computerized Tomography Method: Case Report - İbrahim Yavuz; Bedri Seven; İsmail Ceylan (Galenos Yayinevi, 2006)
The purpose of the present study is to assess the bone activity occurring in the sutures biomechanically activated by facial mask. A tubinger type facial mask was applied to a 16-year-old female child with Class III anomaly, who had completed her pubertal growth spurt. SPECT records were taken before and 6 months after treatment. It was observed in the measurements that there appeared significant increases in right and left sides of zygomatico-maxillary suture and outer zygomatico-maxillary area. These increases demonstrate stimulated bone activity in those areas.